Biological Rhythms in Mammals; Humans and Naked Mole Rats: (Revised Version) - Appenzeller, Otto; Qualls, Clifford; Bromage, Timothy G. (British Journal of Healthcare and Medical Research, 2023)
Here we show that naked mole rats (NMRs) have an extraordinary survival advantage. We base this statement on a spectral analysis of the time series of measured intervals in the teeth of 3 species (NMRs, Killer Whales, and Modern Humans). We used Fourier decomposition to analyze the variability of these intervals. We find these animals go through their long life without any of the age-associated diseases seen in humans such as osteoporosis or cancer and they show no signs of muscle atrophy or slowing of mobility. Global warming will delay its effects on these animals whereas for humans it is a clear and present danger.